Genetic variability studies for yield and fruit fly resistance in bitter gourd(Momordica Charantia L) - Praveena V S (Department of Plant Breeding and Genetics, College of Agriculture, 2010)
A study was undertaken in the Department of Plant Breeding and Genetics, College of Agriculture ,Vellayani during the period 2009-2010 to assess the genetic variability for different yield attributes and resistance to fruit fly in bitter gourd and to identify high yielding genotypes tolerant to fruit fly. To attain these objectives field and laboratory experiments were carried out simultaneously.